(untitled) (Comprehensive Journal of Science, 2025)
Solid waste is one of the environmental problems facing us today, which is one of the most important causes of environmental pollution, especially hazardous waste, due to its harmful effects on human health and safety and the environment alike. Libya, like other countries, suffers from the problem of solid waste accumulation, whether in urban or rural cities. However, recently, it has turned to recycling most of the waste such as (plastic, iron, and paper) and using it to produce various raw materials; Thus, reducing the volume of waste and disposing of it in an environmentally safe manner and achieving environmental security, and from this standpoint came this study in which we shed light on solid waste specifically as one of the most dangerous types of waste, as we initially addressed the concept of solid waste with a statement of its types, the harmful effects caused by this waste, and methods of treating it, as well as explaining the methods used in recycling and their repercussions on environmental security, and explaining the relationship between environmental security and recycling solid waste, and finally this study concluded with a set of recommendations that included improving infrastructure and waste management, as well as recommending strengthening recycling programs, allocating special places for disposing of this waste, and increasing awareness among members of society.